The Research Director's handbook - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Research management for development by John L Nickel 1989 129pp ISBN 92-9039-154-5 pbk Published by The Editorial Service of the Inter-American Institute for Cooperation on Agriculture San Jose, COSTA RICA